Components of curriculum supervision regarding the accountability of universities of medical sciences - Maryam Avizhgan; Nikoo Yamani; Athar Omid; Shahrzad Shahidi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: This study was conducted on accountability, aiming to design components for monitoring the curricula of universities of medical sciences. MATERIALS AND METHODS: This study was a developmental one, conducted in Isfahan University of Medical Sciences with the document and literature review, a focus group, and a survey from 2018 to 2020. The first version of the components was designed by the library research and content analysis method. Following developing the initial tool, its validity was evaluated with a focus group, and the questionnaire was prepared according to face and content validity. RESULTS: In this study, 73 components were designed in eight domains for curriculum supervision, including requirements (12), needs and goals (6), content (10), teaching-learning strategies (10), educational materials and resources (5), educational time (2), educational setting (10), and evaluation (18). CONCLUSION: The components of curriculum supervision were designed due to their importance in the evolution and innovation of medical sciences, particularly accountability in the education system, and lack of relevant research. With these components, the current and optimal status of curricula can be determined in universities.